Characterization and comparison of Porphyridium sordidum and Porphyridium purpureum concerning growth characteristics and polysaccharide production - Medina-Cabrera, Edilberto Vicente (2020)
Microalgae as photosynthetic microorganisms are the source of valuable compounds such as proteins, carotenoids, lipids and carbohydrate polymers. Among the different phyla, Porphyridium as part of the red microalgae (Rhodophyta) are of high importance as producers of sulfated polysaccharides. As the name suggests these microalgae are typically red; however, Porphyridium sordidum has an olive-green color and was recently described as a putative exopolysaccharide producer. Exopolysaccharides (EPS) are sugars polymers excrete to the culture medium. In this study P. sordidum is evaluated for the first time in detail as newly described EPS producer in direct comparison to the already characterized EPS producer Porphyridium purpureum. The evaluation was performed on several aspects, such as morphological differences between the two strains followed by the comparison of the growth behavior, nitrate and phosphate uptake during cultivation of both strains, and a detailed analysis of the EPS. P. purpureum consumed 51 ± 4.6% of nitrate and 95 ± 2.1% of phosphate compared to P. sordidum which utilized 17 ± 0.1% of nitrate and 68 ± 0.1% of phosphate at day 30 of cultivation. The produced EPS were analyzed and revealed the major constitutional carbohydrate monomers of the EPS to be xylose, galactose, glucose and glucuronic acid. In addition, other substituents that decorate the EPS were identified as sulfate and methyl groups. Finally, rheological measurements (viscosity curves and amplitude sweeps) were performed to analyze the physicochemical properties.